THE INFLUENCE OF HORENSO CULTURE ON COMPANY PERFORMANCE IN PT RUNZUNE SAPTA CONSULTANT - Udi Iswadi; Mahfudoh; Erlina Sari Pohan; Zaenudin (AMAL INSANI (Indonesian Multidiscipline of Social Journal), 2021)
This study aims to determine and analyze the influence of communication culture known as Horenso (Houkoku, Renraku, Soudan) on company performance. This cultural communication system was introduced from Japanese industries in Indonesia. Theoretically, a good communication system is a challenge to be competitive in the economy. The communication that is built will create a culture within the company, resulting in dynamics and harmonization which ultimately aims at the company's target in the form of achieving performance. This study uses primary data by distributing questionnaires to respondents, namely employees of PT Runzune Sapta Consultant from a population of 430 employees and a sample of 81 employees. Sampling was carried out using a random sampling technique with an error tolerance limit of 10%. The analysis in this study uses a correlation technique. The results of this study indicate that there is an influence of Horenso culture on company performance at PT Runzune Sapta Consultant, it can be seen from the results of several tests, namely the analysis of the X variable (Horenso Culture) on the Y variable (Company Performance) by using product moment correlation analysis to obtain a value. of 0.690 means that it has a strong correlation between Horenso culture on company performance.